Seasonal Growth and Trends of Food Grains in India; Yield, Area, and Production: A Structural Stability Regression Model Approach (International Journal of Food and Nutritional Sciences, 2022)
The area and yield of agricultural output throughout the kharif and rabi seasons, as well as the growth, trend, and structural stability of agricultural production of food grains, represent an economy's structural stability and contribution to GDP. This study aims to assess the growth, trend, and structural stability of food grain production in India throughout the kharif and rabi seasons before (1980-2000) and after the implementation of the new agricultural policy (2001-2020). Secondary data was acquired to achieve the objectives from the Agricultural Statistics at a Glance—2021, Government of India—the Ministry of Agriculture and Farmers' Welfare—the Directorate of Economics and Statistics. The structural stability regression model, t test, and trend line were used to estimate and compare the growth of food grain output, area, and yield. According to the study, the area, production, and yield growth rates from 1980 to 2020 were -14.84, 85.20, and 117.47 percent in kharif, 29.15, 195.89, and 129.12 percent in rabi, and 0.253, 129.57, and 129.03 percent in total food grains. Additionally, the study found that India's food grain production and area under cultivation had undergone structural change throughout time. In order to produce more food grains, there has been an increase in area, a higher yield per hectare, and changes in production methods. The focus of policymakers should be on enlarging the area by making effective use of available land, increasing production through technological advancements, research in agriculture, and instruction, as well as accelerating the execution of policies in India.